Phytoremediation - A Promising Technique in Waste Water Treatment - M. Anji Reddy, K. Sri Lakshmi, V. Hema Sailaja, (International Journal of Scientific Research and Management (IJSRM), 2017)
Water being the source of life has become a scarce resource in this millennium. Since the limited resource availability, reuse of the available supply is more suggestible. For the said goal, many technologies prevail addressing the task, among which is the technique Phytoremediation. Loads of waste waters gets generated from industrial, commercial and domestic origins and is discarded. Phytoremediation converts this waste water into usable water with the help of plants. This is a very ecofriendly technique which decontaminate the waste water in a very economical way. This review article thus emphasizes on this technique process in detail with special emphases on recent studies carried out for Industrial wastewater treatment. The main conclusions arrive at focusing to develop better economic models to handle abundant quantities of wastewater with varied characteristics, overall decontamination efficiency when compared with other conventional techniques..